Preparation method of Ag nanoparticle modified WO3 nanospheres for high-sensitivity detection of H2S gas
By modifying Ag nanoparticles on WO3 nanospheres, and using the sensitization effect of Ag NPs, the existing WO3-based H2S gas sensors have high working temperature and low response value, achieving high sensitivity, rapid response and room temperature detection effects .
Patent Information
- Application Number
- CN202411304589.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-09-19
AI Technical Summary
The existing WO3-based H2S gas sensors have the disadvantages of high operating temperature, low response value, and poor selectivity, making it difficult to achieve the effects of high sensitivity, rapid response and room temperature detection.
Ag nanoparticles were synthesized by solvent heat plus sodium borohydride (NaBH4) reduction method to modify WO3 nanospheres, and the electron sensitization and chemical sensitization effects of Ag NPs were used to improve the gas sensitivity performance of gas sensors.
The response value and sensitivity of the H2S gas sensor are significantly improved, with the detection lower limit as low as 10ppb and the response time is only 6s, achieving efficient detection of H2S gas at room temperature.
Smart Images

Figure CN119430285A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas sensors, and in particular relates to a method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas. Background Art
[0002] Hydrogen sulfide (H2S) is a toxic, harmful, flammable and explosive acidic gas. Long-term exposure to it can cause harm to human life and health. [1] Inhaling low concentrations of H2S gas can cause inflammation, pulmonary edema, respiratory tract infection and other physiological diseases. Once the concentration exceeds 10ppm, it can cause loss of smell, breathing difficulties and even death. [2] Therefore, for safety reasons, the Occupational Safety and Health Administration (OSHA) has set the safe exposure limit for H2S at 20ppm. [3 In addition, H2S can also be used as a biomarker for the diagnosis of medical diseases. For example, the exhaled gas of patients with halitosis generally contains ~0.1-0.5ppm H2S, which can be used as a biomarker for the diagnosis of tongue coating, mucosal diseases, periodontal diseases and other diseases. [4] The H2S concentration in the exhaled breath of patients with hepatocellular carcinoma (HCC) is 23 ppb [5] Traditionally, bad breath can be monitored through the sensory system, but H2S at concentrations as low as ppb cannot be detected by the human olfactory system. Fortunately, the use of gas sensors to detect biomarkers such as H2S has become an emerging technology, which has also promoted the rapid development of gas sensors and smart medical fields. [6] .
[0003] As a typical n-type MOS, WO3 is widely used in gas sensor research due to its low price, easy structure control, non-stoichiometric characteristics and high gas sensitivity. [7-9 ]. Through literature research, it can be learned that although pure phase WO3 can effectively detect toxic and harmful gases, it still has disadvantages such as high operating temperature, low response value, and poor selectivity, which limits its detection of H2S gas. [10-1 2]. Currently, WO3 materials with different morphologies and structures have been widely used to detect H2S gas. Zhu et al.
[13] The WO3 nanofilm was prepared on the electrode sheet using magnetron sputtering technology. In the two-month test of H2S, the response value of the WO3 sensor only decreased by 3.1%, showing good long-term stability.
[14] WO3 nanoflowers with a hierarchical structure were synthesized, showing high sensitivity to H2S gas and low operating temperature.
[0004] Although the gas sensing performance can be improved by changing the morphology of WO3, this improvement is limited. We can also further improve the sensing performance of WO3 by adding precious metal catalysts. [15 ]. Currently, common noble metal modified WO3-based H2S gas sensors mainly include Au, Pt, Pd, Ru, etc., while there are very few reports on Ag-modified WO3-based gas sensors. Choi et al. [16 ] prepared Pt nanoparticle-modified WO3 nanofibers for pattern recognition of simulated respiratory gas components. The results showed that the response value to 5 ppm H2S at 350°C was as high as 834.2, and the sensitivity and selectivity were significantly improved. Guo et al. [1 7] used electron beam evaporation to deposit WO3 and Pd sequentially on an alumina substrate, providing an effective strategy for achieving high-performance H2S sensors with ppb-level detection limits. Kruefu et al. [18 ] synthesized a series of WO3 sensors with different Ru concentrations. The Ru-functionalized WO3 nanomaterials optimized the sensor's response value, response / recovery time, and selectivity. In addition to single noble metal modification, dual noble metal modification also showed excellent gas sensing performance. Zhang et al. [19 ] used hexagonal WO3 nanorods co-modified with Pt and Pd to evaluate the gas sensing performance of H2S gas. At 120°C, the response value of PtPd@h-WO3 sensor to H2S was about 49.47 times that of pure WO3 sensor. In addition, Gui et al.
[20] The prepared Ag / WO3 / rGO sensor also exhibited good gas-sensing performance to H2S gas, which was significantly better than that of WO3 / rGO.
[0005] It can be seen that the strategy of noble metal modified WO3 gas sensor can fully improve the gas sensing performance of H2S detection, but it also has disadvantages such as high working temperature. Therefore, the development of high-sensitivity, high-selectivity, fast-response, room-temperature H2S gas sensor has become an urgent problem to be solved.
[0006] References
[0007] [1]M.Yu,J.Li,D.Yin,Z.Zhou,C.Wei,Y.Wang,J.Hao,Enhanced oxygen anionsgeneration on Bi(2)S(3) / Sb(2)S(3)heterostructure by visible light for trace H(2)S detection at room temperature,JHazard Mater,476(2024)134932.
[0008] [2]P.Hu,J.Chen,Q.Ma,J.Yin,D.Zhou,C.Kou,J.Xu,J.Xu,One-step thermalcompensation decomposition synthesis of ZnWO4 / WO3 composite with synergy ofmultiple structural effects for efficient trace H2S detection,Sensors andActuators B:Chemical,381(2023)133388.
[0009] [3]S.Kundu,G.Gorthala,R.Ghosh,Room Temperature Detection of H2S byTwo Dimensional WS2 based Chemiresistive Sensors,Sensors and Actuators B:Chemical,416(2024)136018.
[0010] [4]D.Feng,L.Du,X.Xing,C.Wang,J.Chen,Z.Zhu,Y.Tian,D.Yang,HighlySensitive and Selective NiO / WO3 Composite Nanoparticles in Detecting H2SBiomarker ofHalitosis,ACS Sensors,6(2021)733-741.
[0011] [5]X.R.Zhu,J.Q.Zhu,Y.F.Chen,Y.Y.Liu,J.J.Lu,J.Sun,S.Q.Peng,M.B.Chen,Y.P.Du,Bioinformatics analysis and experimental verification ofthe prognosticand biological significance mediated by fatty acid metabolism related genesfor hepatocellular carcinoma,Frontiers in oncology,12(2022)972744.
[0012] [6]M.M.a.A.J.Baeumner*,A Megatrend Challenging Analytical Chemistry:Biosensor and Chemosensor Concepts Ready for the Internet of Things,Chemicalreviews,119(2019)7996-8027.
[0013] [7]Y.Wang,S.Zhang,D.Xiao,S.Wang,T.Zhang,X.Yang,S.Heng,M.Sun,CuO / WO3hollow microsphere P-N heterojunction sensor for continuous cycle detectionofH2S gas,Sensors andActuators B:Chemical,(2022)132823.
[0014] [8]S.S.Shendage,V.L.Patil,S.A.Vanalakar,S.P.Patil,N.S.Harale,J.L.Bhosale,J.H.Kim,P.S.Patil,Sensitive and selective NO2 gas sensor based onWO3nanoplates,Sensors andActuators B:Chemical,240(2017)426-433.
[0015] [9]G.-L.Chen,H.-Y.Jiang,Z.-P.Deng,Y.-M.Xu,L.-H.Huo,S.Gao,Controllableassembly ofcorn cob-like h / γ-WO3 hierarchical structure for enhancedsensitive detection of dibutylamine vapor,Sensors and Actuators B:Chemical,415(2024)135981.
[0016]
[10] Y.Ren,Y.Deng,Z.Wang,Y.Li,H.Yu,Y.Zou,L.Wu,Y.Deng,Lab-on-DeviceSynthesis ofHierarchical Macro / Mesoporous WO(3)Semiconducting Films for High-Performance H(2)S Sensing,Small,(2024)e2311659.
[0017]
[11] X.-T.Yin,P.Lv,J.Li,A.Jafari,F.-Y.Wu,Q.Wang,D.Dastan,Z.Shi,S.Yu,H.Garmestani,Nanostructured tungsten trioxide prepared at various growthtemperatures for sensing applications,Journal ofAlloys and Compounds,825(2020)154105.
[0018]
[12] T.Zhao,Y.Fan,Z.Sun,J.Yang,X.Zhu,W.Jiang,L.Wang,Y.Deng,X.Cheng,P.Qiu,W.Luo,Confined interfacial micelle aggregating assembly oforderedmacro–mesoporous tungsten oxides for H2S sensing,Nanoscale,12(2020)20811-20819.
[0019]
[13] C.Zhu,T.Lv,H.Yang,X.Li,X.Wang,X.Guo,C.Xie,D.Zeng,Influence ofmagnetron sputtering process on the stability of WO3 thin film gas sensor,Materials Today Communications,34(2023)105116.
[0020]
[14] M.Sun,S.Zhang,Z.Zhang,H.Zhang,Y.Wang,X.Jing,X.Song,Effect ofC6H14N2O7 and reaction temperature on sensing properties ofhierarchical WO3for H2S sensor,Journal ofMaterials Science,56(2021)11801-11813.
[0021]
[15] L.-Y.Zhu,L.-X.Ou,L.-W.Mao,X.-Y.Wu,Y.-P.Liu,H.-L.Lu,Advances inNoble Metal-Decorated Metal Oxide Nanomaterials for Chemiresistive GasSensors:Overview,Nano-micro letters,15(2023).
[0022]
[16] S.-J.Choi,K.H.Ku,B.J.Kim,I.-D.Kim,Novel Templating Route Using PtInfiltrated Block Copolymer Microparticles for Catalytic Pt FunctionalizedMacroporous WO3 Nanofibers and Its Application in Breath Pattern Recognition,ACS Sensors,1(2016)1124-1131.
[0023]
[17] Y.Guo,B.Liu,Z.Duan,Z.Yuan,Y.Jiang,H.Tai,Batch fabrication ofH2Ssensors based on evaporated Pd / WO3 film with ppb-level detection limit,Materials Chemistry and Physics,302(2023)127768.
[0024]
[18] V.Kruefu, A.Wisitsoraat, A.Tuantranont, S.Phanichphant, Ultra-sensitive H2S sensors based on hydrothermal / impregnation-made Ru-functionalized WO3nanorods, Sensors and Actuators B: Chemical, 215 (2015) 630-636.
[0025]
[19] Y.Zhang, J.Chang, Y.Wang, Mechanism analysis of PtPd-decoratedhexagonal WO3 nanorods for H2S sensing application with ppt-level detectionlimit, Journal of Alloys and Compounds, 892(2022)162133.
[0026]
[20] Y. Gui, J. Wu, K. Tian, H. Guo, X. Qin, Summary of the invention
[0027] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas. The WO3 nanospheres modified with precious metal Ag nanoparticles (NPs) with controllable morphology and size are synthesized by a simple solvent thermal plus sodium borohydride (NaBH4) reduction method. The electronic sensitization and chemical sensitization effects of Ag NPs accelerate the charge transfer rate and reduce the reaction activation energy, thereby significantly improving the gas sensing performance of the gas sensor.
[0028] The present invention solves the technical problem by the following technical solutions:
[0029] A method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas, the method comprising the following steps:
[0030] S1. Measure 20-40 mL of ethanol and pour it into a 100 mL beaker. Then add 1.30-1.34 g of WCl6 into the beaker and stir with a magnetic stirrer to fully dissolve it in the ethanol solution to obtain a mixed solution.
[0031] S2, add 2.4-2.6 mmol of diammonium hydrogen citrate (C6H 14 O7N2, polyvinyl pyrrolidone PVP and silver nitrate AgNO3, the amount of silver nitrate AgNO3 added is 0.002828-0.01131g, stirring continuously to make it fully mixed, and finally adding sodium borohydride NaBH4 to obtain a precursor solution;
[0032] S3, transferring the precursor solution into a 50 mL polytetrafluoroethylene reaction container and placing it in an oven for hydrothermal reaction;
[0033] S4, after the reaction is completed, the mixture is cooled naturally, and centrifuged and washed with deionized water and anhydrous ethanol to obtain a precipitate A;
[0034] S5. Dry the precipitate A in a constant temperature vacuum drying oven for 6 to 10 hours, and calcine it in a muffle furnace to obtain light yellow Ag-WO3 nanospheres.
[0035] Moreover, the magnetic stirring time in S1 is 25 to 35 minutes.
[0036] Moreover, the stirring time in S2 is 85 to 95 min, and the molar ratio of AgNO3:NaBH4:PVP is 1:1.2:5.
[0037] Moreover, the oven temperature in S3 is set to 90-110° C., and the hydrothermal reaction time is 23-25 hours.
[0038] Moreover, the centrifugal speed in S4 is 2000-4000 r / min, and the product is first centrifugally washed with deionized water for 2-4 times, and then centrifugally washed with anhydrous ethanol for 2-4 times.
[0039] Moreover, the temperature of the constant temperature vacuum drying oven in S5 is 50-70°C, the vacuum degree is 700-800Pa, the heating rate of the muffle furnace calcination is 2°C / min, and the calcination time at 440-460°C is 110-130min.
[0040] The positive effects that the present invention can produce are:
[0041] 1. The present invention uses solvent heat plus sodium borohydride NaBH4 reduction method to synthesize WO3 nanospheres modified with precious metal Ag nanoparticles (NPs) with controllable morphology and size.
[0042] 2. The Ag-WO3 sensor of the present invention has an ultra-high response value (Ra / Rg=2849) to 10 ppm H2S gas, which is about 235 times that of pure WO3, and is superior to the Ag-WO3 sensors on the market.
[0043] 3. The Ag-WO3 sensor of the present invention can continuously detect 0.01-40ppm H2S gas, with a detection limit as low as 10ppb and a response time of only 6s, and has strong engineering practicability.
[0044] 4. The present invention realizes the development of room temperature sensors. Due to the electronic sensitization and chemical sensitization effects of Ag NPs catalysts, the adsorption rate is improved and the working temperature is reduced, thus realizing the detection of H2S at room temperature (25°C). BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 (a) is a synthesis diagram of WO3 and Ag-WO3 of the present invention, Figure 1 (b) is a test system diagram of the Ag-WO3 gas sensor of the present invention;
[0046] Figure 2 XRD spectra of WO3 and Ag-WO3 materials of the present invention;
[0047] Figure 3 (ab) is the SEM scanning electron microscope image of WO3 of the present invention, Figure 3 (cd) is the SEM scanning electron micrograph of 0.5 mol% Ag-WO3 of the present invention, Figure 3 (e) is the SEM scanning electron microscope of 1.0 mol% Ag-WO3 of the present invention, Figure 3 (f) is the SEM scanning electron microscope of 1.5 mol% Ag-WO3 of the present invention, Figure 3 (gh) is the SEM scanning electron microscope of 2.0 mol% Ag-WO3 of the present invention, Figure 3 (i-1) is the element mapping diagram of 1.0 mol% Ag-WO3 of the present invention;
[0048] Figure 4 (a) is a transmission electron microscope image of WO3 of the present invention, Figure 4 (bc) is a transmission electron microscope image of 1.0 mol% Ag-WO3 of the present invention, Figure 4 (d) is a high-resolution transmission electron micrograph of 1.0 mol% Ag-WO3 of the present invention;
[0049] Figure 5 (a) is the full XPS spectrum of WO3 and Ag-WO3 of the present invention, Figure 5 (b)~(d) are high-resolution XPS spectra of W4f, Ag 3d, and O1s, respectively;
[0050] Figure 6 (a) is a graph showing the response values of the WO3 and Ag-WO3 sensors of the present invention as a function of the operating temperature when the H2S gas concentration is 10 ppm. Figure 6 (b) is a graph showing the resistance (Ra) of the sensor in air at different operating temperatures of the present invention;
[0051] Figure 7 (ad) is the dynamic sensing characteristic curve of 0.5-2.0mol% Ag-WO3 sensor to 1-40-1ppm H2S gas at 25℃, Figure 7 (e) is the dynamic sensing characteristic curve of WO3 sensor to 1-30-1ppm H2S gas at 40℃. Figure 7 (f) is the response curve of 0.5-2.0mol% Ag-WO3 sensor to 1-40ppm H2S gas at 25℃. Figure 7 (g) is the statistical response curve of 1.0 mol% Ag-WO3 at 25°C and 0.01-1 ppm H2S concentration. Figure 7 (hk) is the response / recovery curve of 0.5-2.0mol% Ag-WO3 sensor under 10ppm H2S gas at room temperature (25℃), Figure 7 (l) is the response / recovery curve of WO3 sensor under 40℃ to 10ppm H2S gas;
[0052] Figure 8 (a) is the selectivity response diagram of WO3 and 0.5-2.0 mol% Ag-WO3 to target gases of different concentrations. Figure 8 (bf) are the responses of 0.5-2.0 mol% Ag-WO3 sensors to 10 ppm H2S at room temperature and different relative humidity;
[0053] Fig. 9 (a) is the long-term stability diagram of WO3 and 1.0mol% Ag-WO3 sensors under 10ppm H2S. Fig. 9 (b) Schematic diagram showing that under 10 ppm H2S, the 1.0 mol% Ag-WO3 sensor responded continuously for 10 times on the second day and for 6 times on the 26th day. DETAILED DESCRIPTION
[0054] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0055] like Figure 1As shown, the present invention relates to a method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas, wherein a WO3 nanosphere gas sensor modified with precious metal Ag nanoparticles (NPs) with controllable morphology and size is synthesized by a simple solvent thermal plus sodium borohydride (NaBH4) reduction method, and the electronic sensitization and chemical sensitization effects of Ag NPs accelerate the charge transfer rate and reduce the reaction activation energy, thereby significantly improving the gas sensing performance of the gas sensor.
[0056] Example 1
[0057] (1) Pour 20 mL of ethanol into a 100 mL beaker. Then add 1.30 g of WCl6 and stir with a magnetic stirrer for 20 min to allow it to fully dissolve in the solution.
[0058] (2) Then add 2.4 mmol of diammonium hydrogen citrate (C6H 14 O7N2) reagent, stirring continuously for 20 min. Transfer the precursor solution to a 50 mL polytetrafluoroethylene reaction container and perform hydrothermal reaction at 90 °C for 23 h.
[0059] (3) After the reaction is completed, the mixture is naturally cooled to room temperature, the supernatant is removed, and the mixture is first centrifuged and washed twice with deionized water and then centrifuged and washed twice with anhydrous ethanol to obtain a precipitate A.
[0060] (4) The sample was then placed in a constant temperature vacuum drying oven and dried at 50 °C for 6 h, and calcined at 440 °C for 110 min with a heating rate of 2 °C / min, to finally obtain light yellow WO3 nanoflower powder.
[0061] (5) Pour 20 mL of ethanol into a 100 mL beaker. Then add 1.30 g of WCl6 and stir with a magnetic stirrer for 20 min.
[0062] (6) Then, 2.4 mmol of diammonium hydrogen citrate (C6H 14 O7N2), polyvinyl pyrrolidone (PVP) and silver nitrate (AgNO3), stirring continuously to make them fully mixed. Finally, sodium borohydride (NaBH4) is added. The amount of AgNO3 added is 0.002828-0.01131g, and the molar ratio of AgNO3:NaBH4:PVP is 1:1.2:5.
[0063] (7) The precursor solution was transferred to a 50 mL polytetrafluoroethylene reaction container and subjected to hydrothermal reaction at 90 °C for 23 h.
[0064] (8) After cooling, remove the supernatant, wash the mixture twice with deionized water and then twice with anhydrous ethanol to obtain precipitate B.
[0065] (9) The sample was then placed in a constant temperature vacuum drying oven and dried at 50 °C for 6 h, and calcined at 440 °C for 110 min with a heating rate of 2 °C / min, finally obtaining light yellow Ag-WO3 nanospheres.
[0066] Example 2
[0067] (1) Pour 30 mL of ethanol into a 100 mL beaker. Then add 1.32 g of WCl6 and stir with a magnetic stirrer for 30 min to allow it to fully dissolve in the solution.
[0068] (2) Then add 2.5 mmol of diammonium hydrogen citrate (C6H 14 O7N2) reagent, stirring continuously for 30 min. Transfer the precursor solution to a 50 mL polytetrafluoroethylene reaction container and hydrothermally react at 100 °C for 24 h.
[0069] (3) After the reaction is completed, the mixture is naturally cooled to room temperature, the supernatant is removed, and the mixture is first centrifuged and washed three times with deionized water and then centrifuged and washed three times with anhydrous ethanol to obtain a precipitate A.
[0070] (4) The sample was then placed in a constant temperature vacuum drying oven and dried at 60°C for 8 h, and calcined at 450°C for 120 min with a heating rate of 2°C / min, to finally obtain light yellow WO3 nanoflower powder.
[0071] (5) Pour 30 mL of ethanol into a 100 mL beaker. Then add 1.32 g of WCl6 and stir with a magnetic stirrer for 30 min.
[0072] (6) Then, 2.5 mmol of diammonium hydrogen citrate (C6H 14 O7N2), polyvinyl pyrrolidone (PVP) and silver nitrate (AgNO3), stirring continuously to make them fully mixed. Finally, sodium borohydride (NaBH4) is added. The amount of AgNO3 added is 0.002828-0.01131g, and the molar ratio of AgNO3:NaBH4:PVP is 1:1.2:5.
[0073] (7) The precursor solution was transferred to a 50 mL polytetrafluoroethylene reaction container and subjected to hydrothermal reaction at 100 °C for 24 h.
[0074] (8) After cooling, remove the supernatant, wash the mixture three times with deionized water, and then wash it three times with anhydrous ethanol to obtain precipitate B.
[0075] (9) The sample was then placed in a constant temperature vacuum drying oven and dried at 60 °C for 8 h, calcined at 450 °C for 120 min, and the heating rate was 2 °C / min, finally obtaining light yellow Ag-WO3 nanospheres.
[0076] Example 3
[0077] (1) Pour 40 mL of ethanol into a 100 mL beaker. Then add 1.34 g of WCl6 and stir with a magnetic stirrer for 40 min to allow it to fully dissolve in the solution.
[0078] (2) Then add 2.6 mmol of diammonium hydrogen citrate (C6H 14 O7N2) reagent, stirring continuously for 40 min. Transfer the precursor solution to a 50 mL polytetrafluoroethylene reaction container and perform hydrothermal reaction at 110 °C for 25 h.
[0079] (3) After the reaction is completed, the mixture is naturally cooled to room temperature, the supernatant is removed, and the mixture is first centrifuged and washed four times with deionized water and then centrifuged and washed four times with anhydrous ethanol to obtain a precipitate A.
[0080] (4) The sample was then placed in a constant temperature vacuum drying oven and dried at 70°C for 10 h, and calcined at 460°C for 130 min with a heating rate of 2°C / min, to finally obtain light yellow WO3 nanoflower powder.
[0081] (5) Pour 40 mL of ethanol into a 100 mL beaker, then add 1.34 g of WCl6 and stir with a magnetic stirrer for 40 min.
[0082] (6) Then, 2.6 mmol of diammonium hydrogen citrate (C6H 14 O7N2), polyvinyl pyrrolidone (PVP) and silver nitrate (AgNO3), stirring continuously to make them fully mixed. Finally, sodium borohydride (NaBH4) is added. The amount of AgNO3 added is 0.002828-0.01131g, and the molar ratio of AgNO3:NaBH4:PVP is 1:1.2:5.
[0083] (7) The precursor solution was transferred to a 50 mL polytetrafluoroethylene reaction container and subjected to hydrothermal reaction at 110 °C for 25 h.
[0084] (8) After cooling, the supernatant was removed and the mixture was washed four times by centrifugation with deionized water and then four times by centrifugation with anhydrous ethanol to obtain precipitate B.
[0085] (9) The sample was then placed in a constant temperature vacuum drying oven and dried at 70 °C for 10 h, calcined at 460 °C for 130 min, and the heating rate was 2 °C / min, finally obtaining light yellow Ag-WO3 nanospheres.
[0086] like Figure 2As shown in the figure, the crystal structure and phase purity of WO3 and Ag-WO3 nanospheres were obtained by XRD analysis. These diffraction peaks have similar characteristics, and the main XRD peaks of pure WO3 and Ag-WO3 materials correspond to monoclinic phase WO3 (JCPDS No.72-0677). The diffraction peaks are located at 23.109°, 23.579°, 24.349°, 33.252°, 34.151°, 49.893° and 55.894°, corresponding to the (002), (020), (200), (022), (202), (400) and (420) crystal planes of monoclinic WO3, respectively. In addition, the characteristic peaks of Ag observed in the Ag-WO3 material are not obvious, which may be due to the low content of Ag NPs, the small crystal size of Ag NPs, and the high degree of dispersion of AgNPs on the surface of WO3 nanospheres, which are difficult to detect. However, it can be found that with the increase of Ag NPs content, the diffraction peaks near 35.50°, 44.75° and 76.6° are significantly enhanced. This is because the diffraction peaks at 35.891°, 45.305° and 76.807° correspond to the (004), (103) and (201) crystal planes of hexagonal Ag (JCPDS No. 41-1402), respectively.
[0087] Figure 3 In the study, the microstructure and phase composition of the material were analyzed using a scanning electron microscope. Obviously, the original WO3 presents a three-dimensional (3D) nanoflower shape self-assembled by nanosheets, and the nanosheets grow outward, which helps to increase the reaction sites of the target gas on the surface of the material ( Figure 3 (ab)). With the addition of AgNO3, PVP and reducing agent NaBH4, the nanosheets on the 0.5mol% Ag-WO3 nanospheres were eroded to a certain extent, the diameter of the nanoflowers was slightly reduced, gaps appeared on the nanoflowers, and there was a tendency to break into nanoparticles ( Figure 3 (cd)). Figure 3The SEM images of (eg) are 1.0mol% Ag-WO3, 1.5mol% Ag-WO3 and 2.0mol% Ag-WO3, respectively. With the addition of AgNO3, PVP and reducing agent NaBH4, the nanoparticles were broken into nanoparticles. The shape of the material became a 3D sphere self-assembled by nanoparticles. Specifically, 1.0mol% Ag-WO3 is a sphere with a diameter of 750nm grown on nanoflowers by assembling 21.1-65.8nm nanoparticles. This special complex structure not only retains the large gas diffusion channels and large specific surface area of nanoflowers. It also provides more surface active sites for gas adsorption. 1.5mol% Ag-WO3 is a sphere with a diameter of about 1.17μm, which is self-assembled from 20.7~41.4nm nanoparticles. However, 2.0mol% Ag-WO3 is a sphere with a diameter of 1.05μm assembled from 39.7-62.2nm nanoparticles. In addition, it can be found that in the magnified SEM image of 2.0 mol% Ag-WO3, the presence of Ag NPs can be clearly seen ( Figure 3 h). Typical element mapping analysis of 1.0mol% Ag-WO3 sample ( Figure 3 (i-1)) further shows that W, O and Ag exist in the sample and are evenly distributed in the sample.
[0088] In order to further verify the structure of the samples, TEM tests were also performed, such as Figure 4 As shown in Figure 2, pure WO3 is a nanoflower-like structure self-assembled from nanosheets, while 1.0 mol% Ag-WO3 is a solid sphere assembled from nanoparticles, and there is also a sheet structure. This is completely consistent with the SEM image characterization. Figure 4 d is the HRTEM image of 1.0 mol% Ag-WO3. The lattice spacings of 0.431 and 0.365 nm correspond to the (111) and (200) planes of monoclinic WO3, respectively, and the lattice spacing of 0.250 nm corresponds to the (004) plane of hexagonal Ag.
[0089] XPS was used to study the elemental configuration and chemical valence state of the material. Figure 5 From the full spectrum of (a), it can be seen that the measured XPS spectrum of the 1.0mol% Ag-WO3 composite surface is composed of Ag, W and O elements, while the measured XPS spectrum of the WO3 surface is composed of W and O elements. In the XPS test, C is used as the reference object. Figure 5 (b) shows the characteristics of W 4f7 / 2 and W 4f5 / 2 at 34.96 and 37.09 eV attributed to 1.0 mol% Ag-WO3, and W4f7 / 2 and W 4f5 / 2 at 34.94 and 37.14 eV attributed to WO3, respectively. +6The existence of has been confirmed. Figure 5 As can be seen in (c), the two peaks at 367.60 eV and 373.60 eV belong to Ag3d5 / 2 and Ag 3d3 / 2, respectively, confirming the presence of Ag. Figure 5 In (d), the O1s spectrum of 1.0 mol% Ag-WO3 has three peaks at 529.70, 530.43, and 532.54 eV, representing lattice oxygen (O L ), oxygen vacancies (O V ) and adsorbed water molecules (O C ). In WO3, the binding energies of these three peaks are 529.75, 531.09 and 532.97 eV, respectively. Compared with WO3, the three O1s peaks of 1.0 mol% Ag-WO3 show negative shifts, and the oxygen vacancies increase. In addition, the relative oxygen content is also different. It can be seen that the oxygen vacancies (O V ) content is higher than that of WO3, which is beneficial to improve gas sensitivity. XPS spectrum confirms that Ag-WO3 is composed of WO3 and metal Ag, which is consistent with the XRD results.
[0090] The contact between the sensitive layer and the gas is closely related to the operating temperature and is an important factor affecting the gas sensing performance of the gas sensor. Figure 6 (a) is the response curve of WO3 and Ag-WO3 sensors with the change of working temperature when the H2S gas concentration is 10ppm. The response value of 0.5-2.0mol% Ag-WO3 sensor decreases with the increase of working temperature, and the response value reaches the maximum value at room temperature. As the working temperature increases, the response value of pure phase WO3 shows a "volcano type", and the response value reaches the maximum value at 40℃. Therefore, the subsequent gas sensing performance test is carried out at room temperature. What is more noteworthy is that under the same room temperature conditions, the gas sensing performance of 0.5-2.0mol% Ag-WO3 sensor is slightly different. The response values (Ra / Rg) of 0.5-2.0mol% Ag-WO3 sensor to 10ppm H2S are 395, 2849, 1570, and 946, respectively, which are much higher than pure phase WO3 (Ra / Rg=12.14). The response value of 2.0mol% Ag-WO3 sensor is the largest, about 235 times that of WO3. This indicates that the WO3 nanosphere sensor modified with AgNPs surface significantly improves the response value of the sensor. Figure 6 (b) shows the relationship between the operating temperature and the Ra value of the sensor. As the operating temperature increases, the Ra of all sensors decreases, showing typical semiconductor characteristics. In addition, it can be clearly seen that at the same operating temperature, the Ra value of the Ag-WO3 sensor is significantly higher than that of the pure phase WO3 sensor, because a Schottky barrier and a thicker electron depletion layer are formed at the interface between Ag and WO3.
[0091] Figure 7 (ae) The continuous response cycle performance of Ag-WO3 and WO3 sensors to H2S gas of different concentrations at 25℃ and 40℃, respectively. In H2S gas of different concentrations, the resistance of the gas sensor loaded with AgNPs drops faster and more sharply than that of the pure WO3 sensor. The response amplitude increases with the increase of H2S concentration. At the same time, in the dynamic test of H2S gas cycle of different concentrations, the concentration response values corresponding to the four sensors are basically the same, indicating that the Ag-WO3 sensor has good short-term reproducibility. It is worth noting that the response value of the 1.0mol% Ag-WO3 sensor is the largest ( Figure 7 (f)), which is much higher than that of pure WO3. The response value of 1.0mol% Ag-WO3 is a function of H2S concentration. More importantly, in the minimum detection limit test ( Figure 7 (g)), 0.5-2.0mol% Ag-WO3 sensors showed good response even in the presence of H2S gas at ppb level, with the minimum detection limit as low as 10ppb and the response values of 1.32, 1.74, 1.3, and 1.09, respectively.
[0092] In addition, the response / recovery capabilities of 0.5–2.0 mol% Ag-WO3 and WO3 sensors were investigated, as Figure 7 (h-1). At the optimal working temperature, the response times of 0.5-2.0mol% Ag-WO3 and WO3 to 10ppm H2S gas are 23, 6, 46, 17 and 30s, respectively. Compared with WO3, the response signal amplitude of 1.0mol% Ag-WO3 material is significantly enhanced, and the response time is shortened from the original 30s to 6s. This may be because silver may provide catalytic centers for the oxidation of adsorbed H2S molecules, injecting electrons into the conduction band of WO3 and changing the conductivity of WO3. After the reaction, due to the strong adsorption of H2S, the sensor cannot be quickly recovered at room temperature, so it is necessary to provide a pulse heating current outside the sensor to accelerate the strong adsorption of Ag and S, so that the H2S molecules are separated from AgNPs. 0.5-2.0mol% Ag-WO3 was heated at 170, 150, 190, and 140℃ for 90s, and WO3 was heated at 80℃ for 60s.
[0093] Ideally, a gas sensor should have the ability to screen for specific gases, so selectivity is a key parameter of a gas sensor, such as Figure 8The selectivity of the sensor was analyzed by measuring the response of WO3 and 1.0mol% Ag-WO3 sensors to 10ppm H2S, SO2, CO, NO2 and 100ppm EG, ethanol, and methanol gases. The 0.5-2.0mol% Ag-WO3 experiment was carried out at room temperature, and the WO3 experiment was carried out at 40℃. The results are shown in Figure 8 (a) As shown in the diagram (radar chart), it is obvious that all 0.5-2.0mol% Ag-WO3 sensors show high contrast in relative response to the test gases, with the highest response to H2S and negligible response to other gases. In addition, the relative humidity of the environment also has an effect on the performance of the gas sensor. Figure 8 (bf) are the response curves of 0.5-2.0 mol% Ag-WO3 sensors to 10 ppm H2S at room temperature and different relative humidity (RH) conditions of 20-77%. Compared with other sensors, the 1.0 mol% Ag-WO3 sensor still has the highest response value at different humidity. However, with the increase of relative humidity, the initial resistance and response values of the four Ag-WO3 sensors all decrease to a certain extent. This may be because under high humidity conditions, on the one hand, a large number of water molecules will react with oxygen ions adsorbed on the surface of the material, releasing electrons into the material body, thereby reducing the Ra resistance value of the sensor. On the other hand, a large number of water molecules will compete with H2S molecules, adsorb active sites on the surface of the sensitive layer, reduce the activity of the material, and thus reduce the response value of the sensor.
[0094] In the stability test, the short-term repeatability and long-term stability of the sensor were studied. Fig. 9 (b) shows the response / recovery curves of 10 and 6 times of exposure to 10ppm H2S at room temperature, 2 days and 26 days respectively. The results show that the response value remains basically unchanged, the baseline resistance can be restored to the original state, and the short-term reproducibility is good. In addition, this work also tested the long-term stability of WO3 and 1.0mol% Ag-WO3 sensors, and at least three cycles were performed in each of the test periods of one month, as shown in Figure 2. Fig. 9 (a). The sensor response value decreases negligibly and the overall baseline remains stable. The increase in the resistance value Ra is also negligible. Good long-term stability has been demonstrated. This negligible change may be due to the fact that the H2S gas cannot be completely desorbed from the material, partially forming WS2 and Ag2S. However, it is worth noting that the response value of the 1.0mol% Ag-WO3 sensor is still much higher than that of the WO3 sensor.
[0095] Although the embodiments and drawings of the present invention are disclosed for illustrative purposes, those skilled in the art will appreciate that various substitutions, changes and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. A method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas, characterized in that: The steps of the method are: S1. Measure 20-40 mL of ethanol and pour it into a 100 mL beaker. Then add 1.30-1.34 g of WCl6 into the beaker and stir with a magnetic stirrer to fully dissolve it in the ethanol solution to obtain a mixed solution. S2, add 2.4-2.6 mmol of diammonium hydrogen citrate (C6H 14 O7N2, polyvinyl pyrrolidone PVP and silver nitrate AgNO3, the amount of silver nitrate AgNO3 added is 0.002828-0.01131g, stirring continuously to make it fully mixed, and finally adding sodium borohydride NaBH4 to obtain a precursor solution; S3, transferring the precursor solution into a 50 mL polytetrafluoroethylene reaction container and placing it in an oven for hydrothermal reaction; S4, after the reaction is completed, the mixture is cooled naturally, and centrifuged and washed with deionized water and anhydrous ethanol to obtain a precipitate A; S5. Dry the precipitate A in a constant temperature vacuum drying oven for 6 to 10 hours, and calcine it in a muffle furnace to obtain light yellow Ag-WO3 nanospheres.
2. The method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas according to claim 1, characterized in that: The magnetic stirring time in S1 is 25 to 35 minutes.
3. The method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas according to claim 1, characterized in that: The stirring time in S2 is 85-95 min, and the molar ratio of AgNO3:NaBH4:PVP is 1:1.2:
5.
4. The method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas according to claim 1, characterized in that: In S3, the oven temperature is set to 90-110° C., and the hydrothermal reaction time is 23-25 hours.
5. The method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas according to claim 1, characterized in that: The centrifugal speed in S4 is 2000-4000 r / min, and the product is first centrifugally washed with deionized water for 2-4 times, and then centrifugally washed with anhydrous ethanol for 2-4 times.
6. The method for preparing Ag nanoparticle-modified WO3 nanospheres for high-sensitivity detection of H2S gas according to claim 1, characterized in that: The temperature of the constant temperature vacuum drying oven in S5 is 50-70°C, the vacuum degree is 700-800 Pa, the heating rate of the muffle furnace calcination is 2°C / min, and the calcination time at 440-460°C is 110-130min.
Citation Information
Patent Citations
NO2 sensor based on precious metal Ag-supported mesoporous WO3 material and preparation method thereof
CN105486724A
Preparation method of silver-phosphate-doped stannic oxide gas sensor gas sensitive material
CN112067666A
Gas sensor for detecting H2S gas
CN115753905A
Method for preparing tungsten trioxide precursor and hydrogen sulfide gas sensor fabricated using the same
US20030099575A1
Flexible nitrogen dioxide gas sensor based on tungsten trioxide nanoparticles coated carbon nanotubes-graphene oxide hybrid and method for manufacturing the same
US20170016867A1